Development and distribution characteristics of ground fissures in high loess filled ground - Yongtang YU; Jianguo ZHENG; Jiwen ZHANG; Zhi LIU (Zhongguo dizhi zaihai yu fangzhi xuebao, 2021)
Fissures are common in high filled ground, it is a potential risk for the safety and stability of engineering sites. Based on the monitoring and detection data of ground fissures in a high loess filled ground in Northern Shaanxi, the development characteristics, distribution regularity and time variation of ground fissures are analyzed, and the formation mechanism of fissures is also discussed according to terrain conditions, thickness of filling and deformation characteristics. The results show that the fissures are mainly developed in the filling ground, and they are distributed in the areas with the thickness less than 15 m and 20 m away from the excavation-filling boundary, the main area is the transition zone between excavation and fill (thickness of excavation and filling is less than or equal to 5 m). The trend of fissures is approximately consistent with the excavation-filling boundary or the contour line of original foundation, the increasing rate of the fissure width decreases gradually, and it takes about 3 months from its appearance to stabilization. The fissures often develop with a sinkhole and extends along the joint surface between the filling and valley slope due to the effect of precipitation erosion and subsurface erosion, with a vertical depth of 7.5 m. The differential settlement and horizontal displacement caused by the difference of gully topography and thickness of filling are the main causes of fissures in high loess filled ground.